The Role of Systems, Management, and Political Policies in the Management of Islamic Education - Achmad Fadlani; Kasful Anwar (Dinasti International Journal of Education Management And Social Science, 2023)
The writing of this article describes an Islamic-based education management system that is influenced by politics. The method used in this writing is literature study by collecting various appropriate references and supporting discussions about systems, management and policies that have an impact on politics. A quality and quality education management system will greatly influence policy in positive terms. One of the impacts discussed in this paper relates to the system of political management in Islam that exists in Indonesia in general. The relationship between educational institutions and political policies is a relationship that requires each other and has a balanced impact as well. Leading to a good management system, policies within the institution will run optimally.